Differences in the timing of diapause and patterns of aestivation in tropical earthworms - Jiménez Jaén, J.J.; Brown, George G.; Decaëns, Thibaud; Feijoo Martínez, Alexander; Lavelle, Patrick M. (International Center for Tropical Agriculture, 2001)
A detailed description and drawings of the aestivation chambers of five earthworm species are given plus a complete analysis of the mechanistic processes that determine this behavioral pattern for one anecic species from Colombia. The onset of aestivation differed in adults and juveniles for two glossoscolecid tropical species, i.e., Glossodrilus n. sp. and Martiodrilus carimaguensis, a native anecic earthworm from the tropical lowlands of Colombia which undergoes diapause by burrowing deep into the soil during late rainy season, while immature individuals enter into this phase 4 months earlier. Relationships between the aestivation period and the addition of new segments in earthworms have been established by several authors. In this study there was no relationship for the only species studied in more detail